2014
DOI: 10.1063/1.4890311
|View full text |Cite
|
Sign up to set email alerts
|

Importance of growth direction in mid-infrared quantum cascade lasers

Abstract: We report on the effect of growth direction on the performance of mid-infrared Quantum Cascade lasers. The design used has a symmetric active core, capable of operating under both negative and positive polarities, which allows to test for residual growth asymmetries such as interface roughness and dopant migration. Calculations of scattering lifetimes from interface roughness and ionized impurities suggest a dominant contribution from the former, with devices biased positively averaging $15% larger broadening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Recent results from direct interface roughness measurements of InGaAs/InAlAs heterojunctions grown by MOCVD show that InGaAs-on-InAlAs interfaces are rougher and more strongly correlated than InAlAs-on-InGaAs ones . Therefore, we expect also a favored operating direction with respect to the growth direction, as recently shown for symmetric InGaAs/InAlAs mid-infrared QCL structures …”
Section: Influence Of Growth-related Asymmetriessupporting
confidence: 69%
See 1 more Smart Citation
“…Recent results from direct interface roughness measurements of InGaAs/InAlAs heterojunctions grown by MOCVD show that InGaAs-on-InAlAs interfaces are rougher and more strongly correlated than InAlAs-on-InGaAs ones . Therefore, we expect also a favored operating direction with respect to the growth direction, as recently shown for symmetric InGaAs/InAlAs mid-infrared QCL structures …”
Section: Influence Of Growth-related Asymmetriessupporting
confidence: 69%
“…21 Therefore, we expect also a favored operating direction with respect to the growth direction, as recently shown for symmetric InGaAs/InAlAs mid-infrared QCL structures. 22 …”
Section: Influence Of Growth-related Asymmetriesmentioning
confidence: 99%
“…We examine the influence of changes to the interface roughness on the gain spectrum and consider the limitations of the rate equation approach when evaluating spectra. Recent work has demonstrated a 15% difference in the width of electroluminescence spectra for mid-infrared QCLs operated under different polarity due to asymmetry in the interface roughness [28]. In this work, L was 6 nm and D was 0.2 and 0.1 nm for the rough and smooth interfaces, respectively.…”
Section: Gain Spectrummentioning
confidence: 69%
“…Studies on symmetric active regions revealed the importance of the position of the dopant atoms within the injector of QCL active regions . The nominally rectangular doping profile is actually smeared out along the growth direction.…”
Section: Growth Optimizationmentioning
confidence: 99%